Use of Thromboelastography in the Evaluation and Management of Patients With Traumatic Brain Injury: A Systematic Review and Meta-Analysis. (14th September 2021) - Cannon, Jeremy W.; Dias, João D.; Kumar, Monisha A.; Walsh, Mark; Thomas, Scott G.; Cotton, Bryan A.; Schuster, James M.; Evans, Susan L.; Schreiber, Martin A.; Adam, Elisabeth H.; Zacharowski, Kai; Hartmann, Jan; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Traumatic brain injury is associated with coagulopathy that increases mortality risk. Viscoelastic hemostatic assays such as thromboelastography (Haemonetics SA, Signy, Switzerland) provide rapid coagulopathy assessment and may be particularly useful for goal-directed treatment of traumatic brain injury patients. We conducted a systematic review to assess thromboelastography in the evaluation and management of coagulopathy in traumatic brain injury patients. DATA SOURCES: MEDLINE, PubMed Central, Embase, and CENTRAL. STUDY SELECTION: Clinical studies of adult patients with traumatic brain injury (isolated or polytrauma) who were assessed by either standard thromboelastography or thromboelastography with platelet mapping plus either conventional coagulation assays or platelet function assays from January 1999 to June 2021. DATA EXTRACTION: Demographics, injury mechanism and severity, diagnostic, laboratory data, therapies, and outcome data were extracted for analysis and comparison. DATA SYNTHESIS: Database search revealed 1, 169 sources; eight additional articles were identified by the authors. After review, 31 publications were used for qualitative analysis, and of these, 16 were used for quantitative analysis. Qualitative and quantitative analysis found unique patterns of thromboelastography and thromboelastography with platelet mapping parameters in traumatic brain injury patients. Patterns were distinct compared with healthy controls, nontraumatic brain injury trauma patients, and traumatic brain injury subpopulations including those with severe traumatic brain injury or penetrating traumatic brain injury. Abnormal thromboelastography K-time and adenosine diphosphate % inhibition on thromboelastography with platelet mapping are associated with decreased survival after traumatic brain injury. Subgroup meta-analysis of severe traumatic brain injury patients from two randomized controlled trials demonstrated improved survival when using a viscoelastic hemostatic assay-guided resuscitation strategy (odds ratio, 0.39; 95% CI, 0.17–0.91; p = 0.030). CONCLUSIONS: Thromboelastography and thromboelastography with platelet mapping characterize coagulopathy patterns in traumatic brain injury patients. Abnormal thromboelastography profiles are associated with poor outcomes. Conversely, treatment protocols designed to normalize abnormal parameters may be associated with improved traumatic brain injury patient outcomes. Current quality of evidence in this population is low; so future efforts should evaluate viscoelastic hemostatic assay-guided hemostatic resuscitation in larger numbers of traumatic brain injury patients with specific focus on those with traumatic brain injury-associated coagulopathy.